MODERN SOCIETY’S (YOUTH GENERATION) PERCEPTION TOWARDS CUSTOM GOVERNMENTAL SYSTEM IN NEGERI KATALOKA, SERAM BAGIAN TIMUR REGENCY, MALUKU - Moh.Mifta Thoha R. Wattimena (IP FS UMY 2016, 2016)
Newly modernized society has undergone various changes in their social order. Their way of production has shifted from agriculture based into industrial based and the way they interact with their neighborhood is change too. However, not all previous system is left behind as we can find in some regions in Indonesia where the custom governmental system is still exist. This thesis tries to explore how Gorom island modern society perceives its custom governmental system with limiting the modern society to the youth generation. This is interesting since the current political studies seems to abandon the discourse on custom and its forms in society. What researcher found in the field does prove that investigating custom as governmental system is very interesting local political studies. Researcher uncovers that modern society in Negeri Kataloka tend to trust and see its government which still exercises custom values as positive thing. By employing three variables—custom, local tradition, government system— as concepts which are used as questions for informants, researcher gets into a conclusion that states the current Kataloka’s custom government is seen positively due to the king role in preserving local traditions wisely.